Perancangan Sistem Informasi di RT 01 RT 06 Kp. Panyingkiran Singaparna Tasikmalaya - Nugraha Yudhasyah; Maya Maryani; Dede Rahmat; Ade Zamzam (LPPM Sekolah Tinggi Teknologi Cipasung, 2022)
RT 01 Kp. Panyingkiran is one of the RTs in Singaparna Village, Singaparna District, Tasikmalaya Regency. In that RT there are problems with recording citizen data and patrol schedules. So far, the registration of citizen data is incomplete, only birth and death data are recorded. Therefore, there are still 2 residents who have died and 3 people who have moved are still registered as residents. Changes to the patrol schedule were not notified, so residents did not know their respective schedules. Therefore, many residents do not follow the patrol schedule. So that there have been 3 times the loss of the motorbike. From these problems, an information system will be designed using the System Development Life Cycle (SDLC) method with the waterfall model. The stages carried out in this model are planning, analysis and design. The design of this system makes it easy for those who need it, so that it can be accessed anywhere and anytime. Then the residents' data and patrol schedules can be seen by the RT head and those who need it, in real time